Supporting Access to Open Online Courses for Learners of Developing Countries - Nti, Kwame (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
This paper examines how access to, and use of, open online courses may be enhanced for learners of developing countries from a learner perspective. Using analysis of the open education concept, factors that affect access to open educational resources content, and universal standards for delivering online learning, the author demonstrates that the open education concept, access, and participation in open online courses follow a three-level relationship. This relationship is affected by technological, economic, and more importantly, social factors, all of which play dual and opposite roles. The open education concept forms the foundation of the three-level relationship, while access maintains a central role from which participation, including use, repurposing, and redistribution of resources depend. The submission is that the relationship among openness, access, and participation should be a major consideration for producers and providers of open online courses who seek to support access for learners of developing countries.